2013
DOI: 10.1080/17470218.2013.853089
|View full text |Cite
|
Sign up to set email alerts
|

Argument disrupts interpersonal synchrony

Abstract: Research on interpersonal convergence and synchrony characterizes the way in which interacting individuals come to have more similar affect, behaviour, and cognition over time. Although its dynamics have been explored in many settings, convergence during conflict has been almost entirely overlooked. We present a simple but ecologically valid study comparing how different situational contexts that highlight affiliation and argument impact interpersonal convergence of body movement and to what degree emotional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
155
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(176 citation statements)
references
References 22 publications
(46 reference statements)
18
155
3
Order By: Relevance
“…As mentioned above, herein we found no evidence o f complexity matching in argumentative conversations, yet there was more behavioral matching compared with affiliative conversations, as measured by peak negative cross correlations. Consistent with this difference, analyses o f move ment dynamics also found no behavioral matching during argu mentative conversations (Paxton & Dale, 2013). In the future we plan to work on complexity matching analyses that may be applied to both movement and speech dynamics, in order to investigate whether multimodal coordination may further illuminate the cou pling of interlocutors during affiliative conversations, and lack thereof during argumentative conversations.…”
Section: Discussionmentioning
confidence: 94%
“…As mentioned above, herein we found no evidence o f complexity matching in argumentative conversations, yet there was more behavioral matching compared with affiliative conversations, as measured by peak negative cross correlations. Consistent with this difference, analyses o f move ment dynamics also found no behavioral matching during argu mentative conversations (Paxton & Dale, 2013). In the future we plan to work on complexity matching analyses that may be applied to both movement and speech dynamics, in order to investigate whether multimodal coordination may further illuminate the cou pling of interlocutors during affiliative conversations, and lack thereof during argumentative conversations.…”
Section: Discussionmentioning
confidence: 94%
“…Social orientation and motivation are malleable and affect coordination. Relevant studies have found that interacting with a late-arriving partner reduced stepping synchronization, compared with interacting with a partner who arrived on time [119], and bodily synchrony decreased during arguments compared with affiliative conversations [120].…”
Section: Social-psychological Factorsmentioning
confidence: 99%
“…Table 1 presents an analysis of methods employed in nearly three dozen published studies that have used shadowing or exposure tasks to assess phonetic convergence. Due to dramatic differences in purposes and methodologies that warrant a separate analysis, the table does not include studies that have examined convergence during conversational interaction (e.g., Abney, Paxton, Dale, & Kello, 2014;Aguilar et al, 2016;Dias & Rosenblum, 2011;Fusaroli & Tylén, 2016;Heldner, Edlund, & Hirschberg, 2010;Kim, Horton, & Bradlow, 2011;Levitan, Benus, Gravano, & Hirschberg, 2015;Levitan & Hirschberg, 2011;Louwerse, Dale, Bard, & Jeuniaux, 2012;Pardo, 2006;Pardo, Cajori Jay, et al, 2013;Pardo, Cajori Jay, & Krauss, 2010;Paxton & Dale, 2013) and under conditions related to longer-term exposure to other talkers, to second language training, or to different linguistic environments (e.g., Chang, 2012;Evans & Iverson, 2007;Harrington, 2006;Harrington, Palethorpe, & Watson, 2000;Pardo, Gibbons, Suppes, & Krauss, 2012;Sancier & Fowler, 1997). Arguably, laboratory speech-shadowing tasks provide a favorable context to elicit phonetic convergence and assess its basic properties (i.e., without interference from conversational goals).…”
Section: Phonetic Convergence In Speech Shadowing Tasksmentioning
confidence: 99%